I Must Buy So I Don’t Die – Panic Buying and Change in Consumer Behavior During COVID-19 in the Pune Metropolitan Region - Khan, Firoz; Kazi, Roshan; Szymanska, Aneta; Singh, Archana (Indian Journal of Marketing, 2023)
Purpose : This article was written with the sole objective of deepening understanding of the relationship that exists between COVID-19 and its effect on the panic buying (PB) behavior of consumers. The study would help in determining factors influencing consumer buying in a pandemic situation. The study hypothesized that psychological factors, perceived product scarcity, and prevailing social conditions (during COVID-19) would trigger PB behavior. This type of consumer behavior could be commonly seen during crises, catastrophic events, epidemics, natural disasters, and public and private health emergencies. Research Design : The type of research is descriptive and conclusive research. We adopted a cross-sectional and deductive approach along with the quantitative research method for evidence-building, accomplished the set research objectives, and gathered relevant data. Structural equation modeling (SEM) was used for model validation. A model comprised of three exogenous variables (perceived fear due to COVID-19 and perceived product scarcity due to COVID-19, prevailing social conditions during COVID-19), one moderating variable (gender,) and one endogenous variable (PB behavior), validated using confirmatory factor analysis (CFA) and SEM. The sample size was justified using the mean method. A convenience sampling technique was used since the sample frame was unavailable. Findings : According to the CFA and SEM, PB behavior arises when negative emotions, including stress, anxiety, and general social unease, directly lead to the creation of fear, social conditions, and perceived scarcity considerations. This influences consumers to make larger purchases than they otherwise would. The gender of an individual plays a very significant role in influencing PB behaviors. The study determined that in the case of men, perceived fear (during COVID-19) positively influenced PB behavior (b = 1.008, p < 0.001), while in the case of women, the relationship between perceived fear and PB behavior (b = 0.177, p < 0.01), the relationship between perceived product scarcity and PB behavior (b = 0.243, p < 0.05), and the relationship between prevailing social conditions (during COVID-19) and PB behavior (b = 0.298, p < 0.001) were significant. Practical Implications : The results of this study would help in influencing retail business policies and understanding the customer better. The study would assist managers in understanding and forecasting the purchasing patterns of both male and female consumers in any pandemic scenario by utilizing the model’s links. The model might be further examined for a variety of samples, and the framework could be re-evaluated in the absence of a pandemic. Originality : This study provided an original scale for measuring the four-model construct to highlight the short- and long-term effects of consumer sentiments. The study was also original and unique in terms of three direct linkages and the moderating effect of gender. It talked about significant managerial implications for industry and theoretical contributions through modeling to the existing body of knowledge.